Evaluating the cascade of care for anal cancer screening within a Ryan White HIV/AIDS Program clinic. (September 2022) - Cardenas, Benjamin F; Geba, Maria; Williams, Brooke; Hoang, Sook; Newberry, Yvonne; Quass-Ferdinand, Laura; Woodberry, Lauren; Dillingham, Rebecca; Thomas, Tania A
Background: Care cascades can inform providers about differences in engagement and retention in care between patient populations thereby improving participation by targeting interventions more effectively. The objective of this study was to assess the uptake and retention of participants along the anal cancer screening algorithm within a single HIV clinic. Methods: Retrospective procedural and demographic data were collected within a Ryan White HIV/AIDS Program clinic from 18 December 2017 to 29 May 2021. A care cascade was constructed among eligible participants who engaged and were retained in the anal cancer screening algorithm. Engagement was defined as having at least one anal Pap smear. Retention was defined as having a follow-up anal Pap smear, and/or high resolution anoscopy, as indicated. Risk ratios (RR) were calculated to reveal factors associated with initiation and retention in screening. Results: Of 821 eligible participants, 312 (38%) engaged in screening and 205 (66%) were retained in care. Anoreceptive intercourse was positively associated with engagement (RR 2.81, 95% confidence interval [CI] 2.05–3.90, p <0.001), whereas male gender was negatively associated (RR 0.26, 95% CI 0.20–0.33, p <0.001). Abnormal cytology results on Pap smear were associated with retention (RR 1.39, 95% CI 1.03–1.86, p =0.03). Conclusions: Overall engagement in anal cancer screening is low within our clinic, particularly among men, but retention in the screening program is notably better, especially among those with abnormal cytology. Target populations have been identified to increase awareness, and qualitative studies are underway to understand perceptions and barriers to engagement in anal cancer screening.